A literature review of washback effects of assessment on language learning - Nguyen Thi Thanh Ha (Ho Chi Minh City Open University Journal of Science - Social Sciences, 2019)
This paper reviews the empirical studies on washback effects of assessment on language learning. The study begins with the definitions of washback, its equivalent terms, and dimensions of washback. Then it summarizes the empirical studies of washback on three most frequently investigated areas, namely learners’ motivation, behaviours, and achievement. Finally, it examines the mechanism by which washback on learning is generated. The findings show how complex and context-dependent test washback is and, based on these findings, the authors provide some recommendations for future research.